Moderators and mediators of change of an internet-based mindfulness intervention for college students: secondary analysis from a randomized controlled trial - Küchler, Ann-Marie; Kählke, Fanny; Bantleon, Leandra; Terhorst, Yannik; Ebert, David Daniel; Baumeister, Harald (Frontiers in Digital Health, 2023)
Background. Existing evidence suggests internet- and mobile-based interventions (IMIs) improve depressive symptoms in college students effectively. However, there is far less knowledge about the potential mechanisms of change of mindfulness-based IMIs, which could contribute to optimizing target groups and interventions. Hence, within this secondary analysis of data from a randomized controlled trial (RCT), potential moderators and mediators of the effectiveness of the IMI StudiCare Mindfulness were investigated. Methods. Moderation and mediation analyses were based on secondary data from an RCT that examined the effectiveness of the 7-module IMI StudiCare Mindfulness in a sample of college students (intervention group: n = 217; waitlist control group: n = 127). Assessments were collected before (t0; baseline), 4 weeks after (t1; during intervention), and 8 weeks after (t2; post-intervention) randomization. Longitudinal mediation analyses using structural equitation modeling were employed, with depressive symptom severity as the dependent variable. For moderation analyses, bilinear interaction models were calculated with depressive symptom severity and mindfulness at t2 as dependent variables. All data-analyses were performed on an intention-to-treat basis. Results. Mediation analyses showed a significant, full mediation of the intervention effect on depressive symptom severity through mindfulness (indirect effect, a*b = 0.153, p < 0.001). Only the number of semesters (interaction: β = 0.24, p = 0.035) was found to moderate the intervention's effectiveness on depressive symptom severity at t2, and only baseline mindfulness (interaction: β = -0.20, p = 0.047) and baseline self-efficacy (interaction: β = -0.27, p = 0.012) were found to be significant moderators of the intervention effect on mindfulness at t2. Conclusion. Our results suggest a mediating role of mindfulness. Moderation analyses demonstrated that the intervention improved depressive symptom severity and mindfulness independent of most examined baseline characteristics. Future confirmatory trials will need to support these findings.